Resourses of open access as a tool for formation of scientific rating of scientists - Chernobay, O. V.; Aksenova, O. Yu. (Science and Transport Progress, 2013)
Purpose. Scientific journals in open access play an important role in scientific communications. It is they are able to provide an operational studying the leading publications and their scientific substantiation in the form of reference to the works of authors that were used in the research. The achievement of high citation index is an important component of scientific activity for the modern scientist. The purpose of the article is to determine the tools to increase the citation index of scientists. Methodology. The methods of generalization, analysis and synthesis, as well as a systematic approach were used in the research. Findings. The university library has an important mission - to distribute the results of research activity of the university scientists. As part of this functional activity area of the scientific and technical library of DNURT a repository of scientific papers, a system of open access for scientific journals and online versions of proceedings were organized. These resources provide the opportunity for a wide range of scientists to study the results of research carried out by their colleagues in DNURT and to cite them in their own articles. During the scientometric research the library staff use the following information platforms: Google Scholar, SciVerse Scopus, DOAJ, Russian Science Citation Index, SCImago Journal & Country Rank. Originality. The work originality is the determination of the ways to influence the formation of the high citation index for scientist. Practical value. The article proves the feasibility of using the open access resources (electronic journals, proceedings and the institutional repositories) to gain the scientist popularity in the professional scientific community.